2018
DOI: 10.21839/jfna.v1i1.113
|View full text |Cite
|
Sign up to set email alerts
|

Kiwifruit under plastic covering: impact on fruit quality and on orchard microclimate

Abstract: Italy has a preeminent rank in kiwifruit industry, being the first exporter and the second largest producer after China. However, in the last few years kiwifruit yields and the total cultivated area considerably decreased, due to the disease spread of the bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa). Bacterial canker has affected significantly orchards productivity and consequently has caused severe economic losses in all major areas of kiwifruit cultivation, including Italy,and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To decrease the influence of environmental conditions that favor pathogen growth, several solutions have been suggested during the last decade, such as the use of fans, under-vine shelters, and overhead irrigation [61,118,119]. Protection against rain, wind, and hail can be provided by the installation of windbreaks (either artificial or natural) and coverings (made of plastic or cloth) to diminish bacterial spread and the incidence of plant wounding [118][119][120]. However, these structures pose added costs to orchard management, and very little is known about how they may affect plant productivity.…”
Section: Edaphoclimatic Conditionsmentioning
confidence: 99%
“…To decrease the influence of environmental conditions that favor pathogen growth, several solutions have been suggested during the last decade, such as the use of fans, under-vine shelters, and overhead irrigation [61,118,119]. Protection against rain, wind, and hail can be provided by the installation of windbreaks (either artificial or natural) and coverings (made of plastic or cloth) to diminish bacterial spread and the incidence of plant wounding [118][119][120]. However, these structures pose added costs to orchard management, and very little is known about how they may affect plant productivity.…”
Section: Edaphoclimatic Conditionsmentioning
confidence: 99%
“…Warmer temperatures, particularly the mean maximum air temperature, together with lower RH and the reduction in rainfall under the nets, can explain the trend of decreased severity of Psa disease symptoms under the photo-selective nets, because these climatic conditions limit the bacteria's development [35]. Air temperatures over 20 • C seem to decrease Psa disease symptoms, as well as the dryer leaves limiting pathogen spread within the canopy [16,18,19]. Moreover, other benefits of the nets include protection from wind and hail that can result in physical damage to the vines, predisposing them to infection [18].…”
Section: Disease Severitymentioning
confidence: 99%
“…actinidiae (Psa) is responsible for high yield losses worldwide [15,16], and environmental stresses such as frost, wind, rain and hail storms are favourable for the spread and development of this disease [15,17]. Plastic covers, as well as photo-selective nets, have emerged as a promising strategy to manage control of Psa [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The color spaces (L*, a*, b*), measured by CIE L*a*b* have been used to evaluate the color of some horticultural products (flowers, fruits, vegetables) (Chiabrando and Giacalone 2018, Teppabut et al 2018, Gracia-Romero et al 2019. Some studies indicated that the color space CIE L*a*b* can be used to study senescence (Teppabut et al 2018, Luo et al 2020 only when the factors that influence the color perception (light intensity, saturation, and angle) are controlled and homogenized (McGuire 1992, Gevers and Smeulders 1999, Gómez-Polo et al 2016.…”
Section: Introductionmentioning
confidence: 99%